MARKETING STRATEGIES FOR ENHANCING MUSIC INDUSTRY VIRALITY THROUGH TIKTOK AND INSTAGRAM - Devanus P. (Suluh Adiluhung Publisher (SAPub), 2026)
This study aims to analyze marketing strategies for increasing the virality of the music industry through the social media platforms TikTok and Instagram. A qualitative approach with a descriptive research method was employed. Data were collected through interviews with music industry practitioners, observations of content on TikTok and Instagram, and documentation. The data were then analyzed using data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that effective marketing strategies include trend research, consistent content creation, active audience engagement, collaboration with influencers, and the effective use of platform features such as Reels, Duets, hashtags, and content performance analytics. However, constantly changing algorithms, intense competition, and the challenge of maintaining long-term audience engagement remain the primary obstacles to increasing music virality through social media.